ANALISIS PENGARUH PERCEIVED CREDIBILITY DAN TRUST TERHADAP ATTITUDE TOWARD SOCIAL MEDIA INFLUENCER SERTA IMPLIKASINYA PADA NIAT PEMBELIAN KOSMETIK HALAL OLEH GEN Z DI JABODETABEK - Zahroh, Dinatul; Arafah, Willy (Promosi: Jurnal Program Studi Pendidikan Ekonomi, 2025)
The halal cosmetics industry in Indonesia has witnessed substantial growth, influenced by the increasing awareness among Generation Z of religious values and the pervasive role of digital platforms. This study aims to examine the influence of perceived credibility and trust on attitudes toward social media influencers (SMIs) and their implications for purchase intention of halal cosmetic products among Gen Z consumers in the Greater Jakarta area (Jabodetabek). A quantitative research method was employed using Structural Equation Modeling (SEM) with AMOS software to analyze the relationships between variables. Primary data were collected through an online questionnaire distributed to 122 Muslim female respondents from Gen Z who actively follow influencers and use halal cosmetics. The findings reveal that both perceived credibility and trust exert a positive and statistically significant impact on attitudes toward SMIs, which in turn significantly influence purchase intention. These results support the applicability of the Theory of Planned Behavior (TPB) in the context of digital halal marketing and emphasize the critical role of influencer credibility and trustworthiness in shaping consumer attitudes and behavioral intentions. This study contributes to the theoretical enrichment of digital consumer behavior literature within a value-driven context and offers practical insights for marketers in developing targeted halal marketing strategies that resonate with Gen Z audiences.